Opening Mosques For Non-Muslims: Muslim Religious Scholars Counter Negative Media Representation Of Terrorism In Kenya - Abdullahi Abdi Sheikh; Bernard Malakwen; Jared Obuya (Universiti Sains Islam Malaysia, 2024)
Al-i’lam - Journal of Contemporary Islamic Communication and Media, Volume 4 Issue 2 Page (141-157)